A dual K+-Na+ selective prussian blue nanotubes sensor - Ang, Jin Qiang (2011)
A strategy for dual sensing of Na+ and K+ ions using Prussian blue nanotubes via selective inter/deintercalation of K+ ion and competitive inhibition by Na+ ion, is reported. The analytical signal is derived from the cyclic voltammetry cathodic peak position Epc of Prussian blue nanotubes. Na+ and K+ levels in a sample solution can be determined conveniently using one Prussian blue nanotubes sensor. In addition, this versatile method can be applied for the analysis of single type of either Na+ or K+ ions. The dual-ion sensor response towards Na+ and K+ can be described using a model based on the competitive inhibition effects of Na+ on K+ inter/deintercalation in Prussian blue nanotubes. Successful application of the Prussian blue nanotubes sensor for Na+ and K+ determination is demonstrated in artificial saliva.